Effect of safety climate relationship, and organizational culture on compliance regulation safety rules - G W Bayutama; S G Partiwi (IPTEK Journal of Proceedings Series, 2018)
Industry competition force companies to compete by optimizing their resources. The use of modern equipment is used to improve the productivity of the company to achieve effectiveness and efficiency. Reliable workforce needed to operate and support the running of modern equipment can meet the desired targets. In the operation of modern equipment it poses a risk of safety hazards and occupational health for the workforce. This risk can threaten the workforce at work, so special attention is needed by all concerned parties such as labor, companies and government.